Predictions and driving factors of production-based CO2 emissions in Beijing, China. (February 2020) - Liu, Zhao; Wang, Fang; Tang, Zhiyao; Tang, Jintong
Highlights: The growth rate of production-based CO2 emissions decreased from 2010 to 2015. Carbon emissions in Beijing will more probably increase in the next decade. The secondary industry scale is the main carbon emission growth factor. Expansion of employment in new and high technology industries reduce emissions. Abstract: China, as the largest emitter of greenhouse gases worldwide, has severe air pollution problems. Emission reduction in metropolises considerably contributes to air quality improvement. In this study, the predictions and driving factors of production-based CO2 emissions in Beijing are analyzed based on regional spatial differentiation. The results show that production-based CO2 emissions in Beijing increased from 12.78 million tons in 1980 to 45.91 million tons in 2015, and the growth rate of CO2 emissions decreased from 2010 to 2015. Moreover, it is probable that the total CO2 emission will rapidly increase by approximately 27 million tons in the following decade. By 2025, the carbon emissions are projected to reach approximately 69.66 million tons with an increase of approximately 23.75 million tons compared with that in 2015. For every 1 % growth in the secondary industry scale, which is the main carbon emission driving factor, CO2 emissions increase by 0.51 %. Population increase and economic development lead to increasing emissions, whereas employment expansion, public transportation system improvement, reduction in household electricity consumption, and waste reduction contribute to emission reduction. This research can be used by policymakers as reference to appropriately target management policies for air pollution control and emission reduction.